Pendampingan Pengisian SPT Tahunan Badan Pada Klien Dan Mitra Melalui PT. Infinity General Consulting - Fatimah, Siti; Yasin, Muaidy; Pascayanti, Yusifa; Faradillah, Lisa; Prajna Wiraputra, Marcellino (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2025)
This community service activity aims to enhance the knowledge and skills of clients and partners in using e-forms for filing Annual Tax Returns (SPT) for corporations. The methods used include lectures, hands-on practice, and discussions. The target audience for this e-form assistance comprises the clients and partners of PT. Infinity General Consulting. The program was conducted over a single day with the support of all employees/staff of PT. Infinity General Consulting. The e-form application is user-friendly, and its output is the Corporate Annual Tax Return for the reporting year. Similarly, the assistance extends to the preparation of financial statements in accordance with accounting standards, particularly the financial accounting standards for MSMEs (Micro, Small, and Medium Entities).Due to time constraints, some clients from the partners still struggle to fully understand the application of the e-form. Therefore, our Community Service Team has created a module and handbook detailing the step-by-step process of filling out the e-form, from the beginning to generating the desired Corporate Annual Tax Return and financial statements. To facilitate communication, the team offers ongoing assistance by providing contact information for the Community Service Team